2015
DOI: 10.31729/jnma.2701
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis Delayed but not Denied - Sheehan’s syndrome

Abstract: Sheehan's syndrome is a rare complication of postpartum hemorrhage. With advancement in obstetric care, Sheehan's syndrome has become uncommon except in developing countries. Here, we report a patient with Sheehan's syndrome who escaped diagnosis for 22 years and presented with life threatening complications. This patient also had certain unusual features of Sheehan's syndrome like pancytopenia and renal failure. A high index of suspicion is necessary in diagnosing such patients. ______________________________… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…Review of literature revealed the rarity of the disorder, with only four cases reported so far. Multiple anterior pituitary hormone deficiencies in Sheehan's syndrome are responsible for pancytopenia; replacement of thyroid and cortisol hormones results in complete recovery [20].…”
Section: Treatmentmentioning
confidence: 99%
“…Review of literature revealed the rarity of the disorder, with only four cases reported so far. Multiple anterior pituitary hormone deficiencies in Sheehan's syndrome are responsible for pancytopenia; replacement of thyroid and cortisol hormones results in complete recovery [20].…”
Section: Treatmentmentioning
confidence: 99%
“…Delayed diagnosis is attributed to the practitioners' inability to link broad spectrum symptomology to the condition. This inability does not stem from indifference, but rather stems from a lack of awareness of the rare condition and the lack of focus on postpartum and menstrual history in the years following delivery [14].…”
Section: Incidence and Prevalencementioning
confidence: 99%
“…The dosage and selection of medication depends on the severity of the imbalance. Some patients need medications only when enduring stress, while others need medications consistently in order to maintain a baseline level [14]. If cortisol levels improve, patients may remain on small doses, increasing the frequency as appropriate [4,23].…”
Section: Breast Atrophy Negativementioning
confidence: 99%
“…[ 1 ] Acute hypopituitarism rarely occurs, and the majority of patients present with nonspecific symptoms in the chronic phase, including fatigue, cold intolerance, sparse axillary and pubic hair, hypopigmentation, and dry skin. [ 2 ] Acute pituitary crisis is mostly caused by infection, trauma, tumors, or surgery. Here, we present a case in which a female developed refractory electrolyte disorders, circulatory collapse, anemia, and coma after lumbar surgery.…”
Section: Introductionmentioning
confidence: 99%